Terrigenous particles regulate autotrophic and heterotrophic microbial assembly and induce humic-like FDOM accumulation in seawater - Zhang, Lianbao; Liu, Yeping; Chen, Li; Song, Hui (Frontiers in Marine Science, 2023)
Climate change can increase riverine discharge, which will promote terrigenous particles transportation and deeply impact microbe-mediated biogeochemical processes in the estuarine ecosystem. However, little is known about the long-term impacts of terrigenous particles on autotrophic and heterotrophic microbial community structures from days to month due to in situ continuous particles inputs. To solve this problem, a large-volume long-term indoor incubation experiment was set up to simulate terrigenous particles inputs scenario. The activity and community structures of keystone groups were largely correlated with biochemical components derived from the terrigenous particles. The ecosystem was maintained by chemoautotrophic nitrifiers before the addition of terrigenous particles. The system was then functionally dominated by heterotrophic microorganisms after the input of terrigenous particles, even though terrigenous particles carried nutrients that could promote the activity of chemoautotrophic microorganisms. The input of terrigenous particles increased the relative intensity of humic-like compounds, mainly through promoting the microbial transformation of organic matter by releasing nutrients and biological labile organic matter to the seawater. This study illustrates that terrigenous particles impact the balance between heterotrophic and chemoautotrophic microbes and play an important role in humic-like compounds transformation in seawater.